Direction and Policies Needed to Support Hybrid Electric Car Research - Subekti, Ridwan Arief; Hartanto, Agus; Susanti, Vita (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2012)
The rising number of vehicles over the years has driven the increase of air pollution and fuel consumption. One of the solutions to overcome this problem is using hybrid electric car because it is environmentally friendly and efficient in fuel consumption. LIPI has conducted electric car research since 1997, but there were so many problems in its development that electric car can not be developed into a national industry scale. Therefore, it is important to conduct a study that maps the problems and finds the solutions to prevent the same failure of electric car commercialization process from happening to hybrid electric car . This study was done by collecting and analyzing the primary and secondary data through interviews, discussing electric hybrid car with stakeholders, and examining earlier study results and regulations. Based on this study, several policies to support sustainability research of hybrid electric car were proposed. Some recommendations were the making of national roadmap and regulation for the usage of hybrid electric car on the road. For policy makers at LIPI, a research focus, research coordination, and pre-commercialization program were recommended.